Prevalence of TP-53/Rb-1 Co-Mutation in Large Cell Neuroendocrine Carcinoma - Saghaeiannejad Esfahani, Hoda; Vela, Cory M.; Chauhan, Aman (Frontiers in Oncology, 2021)
Introduction: Large cell neuroendocrine carcinoma (LCNEC) is a rare and highly aggressive high-grade neuroendocrine neoplasm, which can arise from anywhere in the body. Due to its rarity there is a lacuna in our understanding of LCNEC’s molecular biology. In 2016, Rekhtman and colleagues presented one of the largest molecular sequencing series of pulmonary LCNEC. They differentiated genomic profiles of LCNEC into two major subsets: small cell lung cancer (SCLC)-like, characterized by TP53+RB1 co-mutation/loss, and non-small cell lung cancer (NSCLC)-like, characterized by the lack of co-altered TP53+RB1. This finding is of significance because at present all LCNEC patients are treated like SCLC. However, the universal genomic SCLC biomarker of TP53 and RB1 co-mutation was only found in 40% of their cohort. Since then various other scientists have looked into molecular profiling of LCNEC with markedly discordant results. The objective of this study was to conduct a systematic review of publicly available next generation sequencing (NGS) data to evaluate the prevalence of TP53+RB1 co-mutation in LCNEC. Method: We conducted a literature search using PubMed. Seven studies including 302 patients with pulmonary LCNEC and four studies including 20 patients with extra-pulmonary LCNEC underwent final analysis. Results: The prevalence of TP53+RB1 co-mutation was 36% (109/302) among pulmonary LCNEC patients and 35% (7/20) among the extra-thoracic LCNEC cohort. The universal genomic biomarker of SCLC, TP53+RB1 co-mutation, was found in only 36% of pulmonary LCNEC and 35% of extra-thoracic LCNEC patients. This is in stark contrast to >90% TP53+RB1 co-mutation in SCLC. This is significant since currently majority of LCNEC patients are treated like SCLC. Conclusion: It is now well established that LCNEC is molecularly distinct from SCLC. Prospective studies should be designed to characterize molecular subtypes and direct treatment accordingly.